"CHOICES": An acronym to aid in delineating potential causes of non-metabolic, non-infectious acute toxic leukoencephalopathy. (2019) - Koksel, Yasemin; Ozutemiz, Can; Rykken, Jeffrey; Ott, Frederick; Cayci, Zuzan; Oswood, Mark; McKinney, Alexander M.
Highlights: Recognition the etiologies of ATL is important due to its potentially reversible nature after treatment or removal of the toxin. "CHOICES" is useful to memorize etiologies associated with PVWM injury in non-metabolic and non-infectious ATL patients. Reduced diffusion is an early and important imaging finding to evaluate patients with non-metabolic and non-infectious ATL patients. Abstract: Purpose: To describe non-metabolic, non-infectious etiologies of acute toxic leukoencephalopathy (ATL) on DWI MRI, and provide a useful acronym to remember them. Material and Methods: Our PACS archive was reviewed, yielding 185 patients with suspected ATL per MRI reports and clinical follow up; infectious or metabolic causes were excluded. Result/Discussion: The 87 included non-infectious, non-metabolic ATL patients' etiologies are represented by the acronym 'CHOICES': chemotherapy ('C', n = 34); heroin-induced ('H', n = 6), opioid analogues ('O', n = 14); immunosuppressant ('I', n = 11) or imidazole (n = 2); cocaine ('C', n = 1); environmental or ethanol abuse ('E', n = 5), splenial lesions ('S', n = 9), and 'other' (n = 5). Conclusion: The "CHOICES" acronym delineates various toxic etiologies of ATL.